Jamaica : 2010 First Review of the Stand-By Arrangement; Staff Report; Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2010)
Jamaica has performed well under the Stand-By Arrangement program. Executive Directors commended that overall macroeconomic performance under the program has been encouraging. Directors welcomed the program aimed at fiscal responsibility legislation and central treasury management, public debt restructuring, financial sector reforms, including the improvement of consolidated supervision and the regulation of nonbanks. They agreed that the sale of Air Jamaica represents an important milestone. Based on overall satisfactory performance of Jamaica on completion of the First Review of the SBA, the IMF approved immediate fund disbursement.